1985
DOI: 10.1042/cs0680419
|View full text |Cite
|
Sign up to set email alerts
|

Platelet volume subpopulations in acute myocardial infarction: an investigation of their homogeneity for smoking, infarct size and site

Abstract: Mean platelet volume and count were measured in three groups: patients with acute myocardial infarction, a control group with myocardial ischaemia but no infarction and an asymptomatic group of young males. Mean platelet volume was significantly larger in the myocardial infarction group compared with the ischaemic heart disease group or the asymptomatic group. Two subpopulations were present within the myocardial infarction group. One subgroup had a large mean platelet volume and low count. The other subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1
4

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 0 publications
4
29
1
4
Order By: Relevance
“…In humans, the increased platelet reactivity has been associated with platelet size changes 1 which have been confirmed in recent studies. 3 " 5 This evidence suggests that there may be alterations in platelet production in vascular disease. Two further observations support this hypothesis.…”
mentioning
confidence: 96%
“…In humans, the increased platelet reactivity has been associated with platelet size changes 1 which have been confirmed in recent studies. 3 " 5 This evidence suggests that there may be alterations in platelet production in vascular disease. Two further observations support this hypothesis.…”
mentioning
confidence: 96%
“…So, increased risk of acute coronary syndromes in young patients with high MPV may be explained with the increased activity of platelets, increased inflammation and increased platelet aggregation (19 Many studies of MPV in ACS have been published. In one of them, MPV was found to be elevated in patients with STEMI (20). In another, Pereg et al (21) found an association between unsuccessful thrombolytic therapy and an increased MPV in patients with STEMI.…”
Section: Discussionmentioning
confidence: 95%
“…For example; there is a correlation between the mean platelet volume (MPV) and the functional status of platelets. In many studies, it was showed that MPV was higher in the patients with CAD and acute coronary syndrome in proportion to the normal individuals (Kishk et al, 1985;Bath et al, 1996). Moreover, MPV was detected to be an independent indicator of reperfusion and mortality (Huczek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%